Head-up displays in action video games: the effects of physical and semantic characteristics on player performance and experience. - Caroux, Loïc; Delmas, Maxime; Cahuzac, Marc; Ader, Maylis; Gazagne, Baldéric; Ravassa, Anthony (Behaviour & Information Technology, 2023)
This study aimed to investigate how different characteristics of head-up displays (HUDs) can impact the performance and subjective experience of players in action video games. HUDs are a very common way to display contextual information. However, very few studies have empirically investigated the influence of HUD design on player performance and experience from a human information processing perspective. Four experiments were conducted in which players of different levels of expertise played commercial action video games. The physical characteristics of HUD, that is, the physical appearance of the information on screen, such as size and colour (Experiments 1–2), and the semantic characteristics, that is, the composition (nature and content) of the information (Experiments 3–4), were manipulated. Player performance and subjective experience were systematically assessed. The results showed that players' performance and experience were impacted when the semantic characteristics of the HUD elements were manipulated and when their nature was relevant to the main task players have to perform within the game. The performance of more experienced players was particularly affected in this case. In contrast, the results did not show that altering physical or semantic characteristics that were less relevant to the game's main task would affect players' performance and subjective experience.